Case Report: Two cases of apparent discordance between non-invasive prenatal testing (NIPT) and amniocentesis resulting in feto-placental mosaicism of trisomy 21. Issues in diagnosis, investigation and counselling - Feresin, Agnese; Stampalija, Tamara; Cappellani, Stefania; Bussani, Rossana; Faletra, Flavio; Murru, Flora; Ulivi, Sheila; Suergiu, Sarah; Savarese, Pasquale; Pedicini, Antonio; Policicchio, Margherita; Ruggiero, Raffaella; et al. (Frontiers in Genetics, 2022)
Abstract The sequencing of cell-free fetal DNA in the maternal plasma through non-invasive prenatal testing (NIPT) is an accurate genetic screening test to detect the most common fetal aneuploidies during pregnancy. The extensive use of NIPT, as a screening method, has highlighted the limits of the technique, including false positive and negative results. Feto-placental mosaicism is a challenging biological issue and is the most frequent cause of false positive and negative results in NIPT screening, and of discrepancy between NIPT and invasive testresults. We are reporting on two cases of feto-placental mosaicism of trisomy 21, both with a low-risk NIPT result, identified by ultrasound signs and a subsequent amniocentesis consistent with a trisomy 21. In both cases, after the pregnancy termination, cytogenetic and/or cytogenomic analyses were performed on the placenta and fetal tissues, showing in the first casea mosaicism of trisomy 21 in both the placenta and the fetus, but a mosaicism in the placenta and a complete trisomy 21 in the fetus in the second case. These cases emphasize the need for accurate and complete pre-test NIPT counselling, as well as to identify situations at risk for a possible false negative NIPT result, which may underestimate a potential pathological condition, such as feto-placental mosaicism or fetal trisomy. Post-mortem molecular autopsy may discriminate between placental, fetal and feto-placental mosaicism, and between complete or mosaic fetal chromosomal anomalies. A multidisciplinary approach in counselling, as well as in the interpretation of biological events, is essential for the clarification of complex cases, such as feto-placental mosaicisms.